Pengaruh Brand Image, Life Style dan Trend Terhadap Minat Beli Kopi Kekinian (Studi Kasus di Golden Brown Café, Kecamatan Banyumanik, Kota Semarang) - Sari, Surtika Cahaya; Mariyono, Joko; Prayoga, Kadhung (Universitas Galuh, 2024)
Coffee is an agricultural commodity in the plantation sector that has superior potential in improving the economy in Indonesia. The development of the times makes coffee consumer preferences increasing. And causes business people to be able to adapt to the times in order to be able to maintain their business for consumer interest. This study aims to analyze the influence of “brand image”, “life style” and “trend” on the consumers’ interest to buy contemporary coffee at Golden Brown Café. The study was conducted in February-March 2024 on Golden Brown Café consumers. The research method used in the study is quantitative descriptive, with a total sample of 110 respondents. The data collection method used in this study is by survey method in the form of questionnaires along with using Likert scale in categorizing questions and documentation. Data analysis uses descriptive and multiple linear regression statistics. The result of the descriptive analysis of this study is that “brand image” is dominated by very good responses, “life style” is loaded by good responses, while “trends” responses are not very good. The results of multiple linear regression analysis showed that “brand image”, “life style”, and “trend” partially have a significant and positive effect on buying intent. Simultaneously, “brand image”, “life style” and “trend” have a significant effect on buying intent by yielding determination value of 60.2%.